Community-Based Rainwater Harvesting and Simple Water Treatment System to Improve Domestic Water Security in Rural Indonesia - Muhammad Hakiem Sedo Putra; Kemas Ahmad Kurniawan; Muhammad Syallaby (GIAT Teknologi untuk Masyarakat, 2026)
Limited access to clean water remains a major challenge in many rural areas of Indonesia, particularly during dry seasons when groundwater availability decreases and water quality deteriorates. This community service program was conducted in a rural neighborhood community in Palembang to improve household water security through the implementation of a community-based rainwater harvesting system integrated with a simple gravity-driven filtration unit. The program was implemented using participatory methods, including preliminary assessment, technical design, collaborative construction, community training, and post- installation monitoring. A total of 10 households participated in the program. The installed system consisted of rooftop rainwater collection, a first-flush diverter, storage tanks with capacities of 1000–2000 L, and a slow sand filtration unit constructed from locally available materials. Evaluation results indicated increased water availability during dry periods, reduced dependence on shallow groundwater sources by approximately 30–40%, and improved physical water quality, particularly in reducing turbidity and suspended particles. Community members also demonstrated improved understanding of system operation, maintenance procedures, and hygienic water management practices. The findings show that low-cost and appropriate water technology combined with active community participation can effectively improve domestic water resilience and support sustainable water management in rural communities.